MAKNA SIMBOLIK MITOS DEWI SRI DALAM MASYARAKAT JAWA KAJIAN MODEL LINGUISTIK LEVI-STRAUSS - Suwardi, Suwardi (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 16 (2009): SEJARAH PERKEMBANGAN BAHASA SAKAI, 2009)
Abstract Myth of Dewi Sri in tha Javanese community there are any version believed as fertile idol. For understanding symbolic meaning of myth varian, need of objetive analysis. Than this research try application of linguistic Levi-Strauss model as new strategy for interpretation of myth. Basic assumption from linguistic Levi-Strauss model than myth almost showen varian of surface structure, but it as reflection of man deep structure. The research goal for focused symbolic behind myth of Dewi Sri by point of view of linguistic Levi-Strauss model. Text analyzed two myth Dewi Sri the title of Asal Mula Padi from Banyumas and Sri Sadana from Yogyakarta. Take of two text because near geografis. Take of data mean heuristic reading to two version myth. The data is ceritheme-ceritheme (anthropology diction) and word, frasa, sentence (linguistic). Data analysis by theory of linguistic Levi-Strauss model. The results of research myth Dewi Sri content of varian story is look at by episode and ceritheme. Episode and ceritheme consist of three: (1) gift from God of salvation, (2) incarnation, (3) down of salvation. From episodes can make in the linguistic Levi-Strauss, examples binary oposition, given to message (active), receive of message (passive). Relations between sender and receiver is vertically (structural) it is three structure. From three structure can created three culiner. From three culiner, than Bathara Guru as sender of message. Two myth is not influenced. If any homology or varian, that is same description of Javanese mind.